Iron‐Catalyzed Minisci Type Acetylation of N‐Heteroarenes Mediated by CH(OEt)3/TBHP. Issue 8 (14th February 2019) - Srinivasulu, A.; Shantharjun, B.; Vani, D.; Ashalu, K. Chinna; Mohd, A.; Wencel‐Delord, J.; Colobert, F.; Reddy, K. Rajender
Abstract : Iron‐catalyzed acetylation of electron deficient N‐heteroarenes has been reported using triethylorthoformate as robust and inexpensive acetyl source. This new method is successfully applied for the acetylation of quinolines, isoquinoline, quinoxalines, arylpyridines, bipyridines, and benzothiazole. Abstract : Iron catalysed acetylation of electron deficient N‐heteroarenes has been reported using triethylorthoformateas robust and inexpensive acetyl source. This new method is successfully applied for the acetylation of quinolines, isoquinoline, quinoxalines, arylpyridines, bipyridines, and benzothiazole.